2005
DOI: 10.1158/0008-5472.can-05-0471
|View full text |Cite
|
Sign up to set email alerts
|

Amplification and Overexpression of the KIT Gene Is Associated with Progression in the Seminoma Subtype of Testicular Germ Cell Tumors of Adolescents and Adults

Abstract: We have previously identified amplification at 4q12 in testicular germ cell tumors of adolescents and adults centered around the KIT gene encoding a tyrosine kinase transmembrane receptor. Analysis of primary testicular germ cell tumors totaling 190 cases revealed 21% of the seminoma subtype with an increased copy number of KIT whereas this change was rarely found in the nonseminomas. In most cases, gain of KIT did not include the immediately flanking noncoding DNA or the flanking genes KDR and PDGFRA. Increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
111
3

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 151 publications
(123 citation statements)
references
References 18 publications
9
111
3
Order By: Relevance
“…The function of this pathway was initially discovered in the steel (which encodes SCF) and the dominant white spotting (which encodes cKIT) mouse mutants in which germ cells are lost during the migratory phase. SCF/cKIT signalling is required for proliferation and survival of germ cells and aberrant function of this pathway has been associated with abnormal proliferation and transformation of germ cells Godin and Wylie, 1991;Matsui et al, 1991;Dolci et al, 1993;Pesce et al, 1993;Donovan and de Miguel, 2003;Sakuma et al, 2003;McIntyre et al, 2005;Goddard et al, 2007). Two members of the NANOS family of RNA binding proteins, NANOS2 and NANOS3 are also required for survival of foetal germ cells (Tsuda et al, 2003;Suzuki et al, 2007).…”
Section: Survival and Proliferation: Key Aspects Of Early Germ Cell Dmentioning
confidence: 99%
“…The function of this pathway was initially discovered in the steel (which encodes SCF) and the dominant white spotting (which encodes cKIT) mouse mutants in which germ cells are lost during the migratory phase. SCF/cKIT signalling is required for proliferation and survival of germ cells and aberrant function of this pathway has been associated with abnormal proliferation and transformation of germ cells Godin and Wylie, 1991;Matsui et al, 1991;Dolci et al, 1993;Pesce et al, 1993;Donovan and de Miguel, 2003;Sakuma et al, 2003;McIntyre et al, 2005;Goddard et al, 2007). Two members of the NANOS family of RNA binding proteins, NANOS2 and NANOS3 are also required for survival of foetal germ cells (Tsuda et al, 2003;Suzuki et al, 2007).…”
Section: Survival and Proliferation: Key Aspects Of Early Germ Cell Dmentioning
confidence: 99%
“…24 To determine if the seminomas with c-kit mutations preferentially show increases in c-kit copy number, cases that showed KIT expression (n ¼ 19) were analyzed by c-kit FISH. As shown in Table 1, none of the cases with c-kit mutations appeared to amplify the gene.…”
Section: C-kit Fishmentioning
confidence: 99%
“…KITLG-KIT pathway involvement in TGCTs is supported by numerous evidences: high expression of KIT, somatic activating mutations, and genomic amplification of KIT are frequently seen in TGCTs (especially seminomas; Izquierdo et al 1995, Strohmeyer et al 1995, Bokemeyer et al 1996, Rapley et al 2004, McIntyre et al 2005, Goddard et al 2007; germline deletions of Kitlg increase susceptibility to Table 4 Association of KITLG SNPs with sperm count in testicular germ cell tumor (TGCT) cases and controls TGCTs in mice (Heaney et al 2008); other than KITLG, two of the loci identified by GWAS (SPRY4 and BAK1; Kanetsky et al 2009, Rapley et al 2009 are involved in the KITLG-KIT pathway. The KITLG-KIT system is critical for the correct development of PGCs (Runyan et al 2006, Boldajipour & Raz 2007, the cells from which TGCT is believed to arise.…”
Section: Discussionmentioning
confidence: 93%